Discrete optimization of truss structures using real coded genetic algorithm with hybrid mutation operator - Mohanlal, C.; Anjali, G.; Krishna, N. Murali (Journal of Structural Engineering, 2024)
Efficiency of a genetic algorithm depends on the effectiveness of the genetic operators used in its formulation. In this paper a hybrid mutation operator is introduced to investigate its suitability for design optimization problems. The objective of introducing hybrid mutation operator is to improve population diversity so as to avoid premature convergence. A design procedure incorporating real coded genetic algorithm using discrete design variables is developed for optimizing truss structures. The objective function used here minimizes the truss weight subjected to constraints imposed by strength and serviceability requirements. The utility of the study is demonstrated by comparing the results obtained from the present formulation with earlier research works. Five numerical examples are included in the paper show the efficiency, the accuracy and the applicability of the proposed genetic algorithm, size of the problem notwithstanding.